2021
DOI: 10.1002/jcla.23697
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA UCA1 correlates with elevated disease severity, Th17 cell proportion, inflammatory cytokines, and worse prognosis in acute ischemic stroke patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Data suggested that MIAT might be a potential diagnostic and prognostic indicator in IS ( Zhu et al, 2018 ). LncRNA HULC is correlated with higher AIS risk, increased disease severity, and worse prognosis in AIS patients ( Ren et al, 2021 ). Meanwhile, it associates with higher IL-6, elevated intercellular adhesion molecule 1 (ICAM1), and lower miR-9 AIS patients ( Chen X. et al, 2020 ).…”
Section: Lncrnas As Potential Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%
“…Data suggested that MIAT might be a potential diagnostic and prognostic indicator in IS ( Zhu et al, 2018 ). LncRNA HULC is correlated with higher AIS risk, increased disease severity, and worse prognosis in AIS patients ( Ren et al, 2021 ). Meanwhile, it associates with higher IL-6, elevated intercellular adhesion molecule 1 (ICAM1), and lower miR-9 AIS patients ( Chen X. et al, 2020 ).…”
Section: Lncrnas As Potential Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%
“… 18 , 19 , 20 , 21 While few studies report the roles of lnc‐UCA1, miR‐26a, and miR‐195 in cardiovascular disease patients especially in CHD patients, not to mention the intercorrelation between lnc‐UCA1 and miR‐26a and miR‐195 in these patients. 22 , 23 In our preliminary study with a relatively small sample size, we observed an elevation of lnc‐UCA1 expression in CHD patients compared to controls.…”
Section: Introductionmentioning
confidence: 70%
“…Also, miR‐26a and miR‐195 are two well‐established microRNAs with protective roles in cardiovascular diseases by regulating proliferation, migration, and invasion of vasculature‐related cell (such as endothelial cell and VSMCs) 18–21 . While few studies report the roles of lnc‐UCA1, miR‐26a, and miR‐195 in cardiovascular disease patients especially in CHD patients, not to mention the intercorrelation between lnc‐UCA1 and miR‐26a and miR‐195 in these patients 22,23 . In our preliminary study with a relatively small sample size, we observed an elevation of lnc‐UCA1 expression in CHD patients compared to controls.…”
Section: Introductionmentioning
confidence: 75%
“…A rigorous search of publications on the expression of various lncRNAs in clinical studies published in three electronic databases, namely, PubMed, the Web of Science and EMBASE, until May 31, 2021, identified 6 studies that included 966 participants. [100][101][102][103][104][105] Several lncRNAs have been revealed as novel biomarkers that predict higher or lower stroke risk and contribute to the evaluation of disease severity, inflammation level, and prognosis in stroke participants. 136 Ren et al illustrated that lncRNA MALAT1 decreased and revealed a strong relationship with ischemic conditions, and a higher level was positively associated with a changed National Institutes of Health Stroke Scale (NIHSS) score and induced IL-10 in 200 ischemic stroke cases.…”
Section: Lncrna Regulation Correlates With the Level Of Inflammatory Cytokines In Stroke Patientsmentioning
confidence: 99%